Convention by-laws and regulations of the International "Geneva Association" of Hotel and Restaurant Employees. Founded at Geneva in 1877. Edition 1908 (N.pl.)
With: Statuts conventionnel de l'Union Genevoise Société Internationale d'Employés d'Hotel et Restaurant.